(untitled) (GEOgraphia, 2010)
Este artigo propõe tratar dos conceitos de Distritos Industriais e Clusters. A idéia básica procura analisar em que medida o assim chamado "ABCD Paulista" pode ser considerado um Distrito Industrial ou um Cluster. Tentamos analisar os principais padrões organizacionais da atividade industrial nos quatro municípios que formam o ABCD Paulista. Na mesma linha de raciocínio discutem-se possíveis mudanças futuras, incluindo impactos dessas mudanças na política fiscal. Abstract The present article deals with the concepts of Industrial Districts and Clusters. The main idea behind our analysis is to study in which measure the so called "ABCD Paulista" can be considered as an Industrial District or a Cluster. We try to analyze the main organizational patterns of the industrial activity in the four municipalities that compound the ABCD Paulista. In the same line of reasoning we discuss severa1 possible changes towards the near future, including the impacts of changes in local taxes.